Anatomical and hormonal description of rootlet primordium development along white lupin cluster root. Issue 1 (26th July 2018) - Gallardo, Cécilia; Hufnagel, Bárbara; Casset, Célia; Alcon, Carine; Garcia, Fanny; Divol, Fanchon; Marquès, Laurence; Doumas, Patrick; Péret, Benjamin
Abstract : Cluster root (CR) is one of the most spectacular plant developmental adaptations to hostile environment. It can be found in a few species from a dozen botanical families, including white lupin ( Lupinus albus ) in the Fabaceae family. These amazing structures are produced in phosphate‐deprived conditions and are made of hundreds of short roots also known as rootlets. White lupin is the only crop bearing CRs and is considered as the model species for CR studies. However, little information is available on CRs atypical development, including the molecular events that trigger their formation. To provide insights on CR formation, we performed an anatomical and cellular description of rootlet development in white lupin. Starting with a classic histological approach, we described rootlet primordium development and defined eight developmental stages from rootlet initiation to their emergence. Due to the major role of hormones in the developmental program of root system, we next focussed on auxin‐related mechanisms. We observed the establishment of an auxin maximum through rootlet development in transgenic roots expressing the DR5:GUS auxin reporter. Expression analysis of the main auxin‐related genes [TIR, Auxin Response Factor (ARF) and AUX/IAA] during a detailed time course revealed specific expression associated with the formation of the rootlet primordium. We showed that L. albus TRANSPORT INHIBITOR RESPONSE 1b is expressed during rootlet primordium formation and that L. albus AUXIN RESPONSE FACTOR 5 is expressed in the vasculature but absent in the primordium itself. Altogether, our results describe the very early cellular events leading to CR formation and reveal some of the auxin‐related mechanisms.